Estimates of Intrinsic Square Functions on Generalized Weighted Morrey Spaces. (22nd July 2014) - Gao, Guilian; Wu, Xiaomei
Abstract : We prove the boundedness of the intrinsic functions on generalized weighted Morrey spacesM p, φ ( w ), including the strong type estimates and weak type estimates. Moreover, we define the k th-order commutators generated byBMO R n functions and intrinsic functions, and obtain their strong type estimates onM p, φ ( w ) . In some cases, we improve previous results.